Multiple Wormian Bones in the Lambdoid Suture: A Report of Rare Occurrence - Aragão, José Aderval; de Oliveira, Roberto Ferreira; de Sousa Silva, Smilly Oliveira; Riffel, Lucas Inacio; Sant’Anna Aragão, Iapunira Catarina; Sant’Anna Aragão, Felipe Matheus; Borges, Giulianna da Rocha; Reis, Francisco Prado; Mendonça, Deise Maria Furtado de (Brazilian Journal of Case Reports, 2024)
Wormian bones are irregular bony structures developed from independent ossification centers located at the junction of the sutures between the cranial bones. Although they are commonly found in healthy individuals, their presence can be associated with pathological conditions. Their number above 10, large size, or mosaic pattern are clinically considered as indicators of several pathological conditions, such as abnormalities in the central nervous system, musculoskeletal system, or metabolic changes throughout the body. Our study aims to report a rare occurrence of 40 Wormian bones found in the lambdoid suture of an adult human skull and provide a literature review. Understanding the presence of Wormian bones is crucial for professionals such as neuroanatomists, neurosurgeons, radiologists, anthropologists, and morphologists, as they may be mistaken for fractures in cases of traumatic brain injury.